Observations on the levels of γG, γA, and γM globulins, anti-A and anti-B agglutinins, and antibodies to Escherichia coli in Down's anomaly. Issue 6 (November 1967) - Adinolfi, M.; Gardner, Brighitte; Martin, Wendy
Abstract : The levels of γG, γA, and γM globulins were estimated in a group of patients with Down's anomaly and in groups of mentally retarded children and normal children, matched for age and sex, using an immunological method. Higher levels of γG globulin were observed in patients with Down's syndrome, in association with a small but significant lower concentration of γM globulin. The titres of anti-A and anti-B agglutinins and antibodies to Escherichia coli, estimated before and after treatment of serum with 2-mercaptoethanol, were found to be within normal levels. These data seem to suggest that patients with Down's syndrome do not produce `faulty' immunoglobulins as has been previously postulated. It is suggested that the abnormal levels of immunoglobulins found in Down's anomaly are not peculiar to patients with Down's syndrome but occur in other disorders in which the reticuloendothelial system or the lymphocytes are involved.